Changes in the level of coordination preparedness of gymnasts 10–12 years as a result of the use of special exercises on the simulator "Bos Balance Trainer" - Дейнеко, Альфія; Красова, Інна (Slobozhanskyi Herald of Science and Sport, 2018)
Alfiya Deyneko & Inna Krasova Purpose: to substantiate the effectiveness of using the developed exercise complexes on the simulator "Bosu Balance Trainer" ("BOSU") for the development of the coordination preparedness of female athletes of 10–12 years in rhythmic gymnastics. Material & Methods: the study involved female athletes 10–12 years old engaged in rhythmic gymnastics. The control and experimental groups consisted of 12 gymnasts. To solve the problems, the following research methods were used: theoretical analysis and generalization of literary sources; pedagogical observations; testing; pedagogical experiment; methods of mathematical statistics. Results: based on the results of the study, a positive effect of the developed exercise complexes on the BOSU simulator on the development of the coordination preparedness of female athletes aged 10–12 in rhythmic gymnastics was revealed. Conclusion: the use of the developed exercise complexes on the BOSU simulator in the rhythmic gymnastics training process positively influenced the development of the level of coordination preparedness of female athletes of 10–12 years.